Administrative reform of Majlis Bandaraya Melaka Bersejarah in term of parking service / Amira Zainura Zainal Abidin and Mohd Khairul Insan Nazri - Zainal Abidin, Amira Zainura; Nazri, Mohd Khairul Insan (Faculty of Administrative Science and Policy Studies, 2008)
Malacca has gone through its ups and downs; the city of Malacca has continued to exist. In 1824, it was called The Town and The Fort of Malacca, administrated by the Committee of Assessors under the English Government. In 1848, The East India Act XIX recommended the formation of a Municipal Committee to replace the Committee of Assessors. The act allocated five council members led by a Resident Councilor which were known as City Councilmen (Pesuruhjaya Perbandaran) The East India Act XXVII gave power to these City Councilmen as trust members in which they could indict or be indicted. In 1.1.1887, The Straits Settlements City Ordinance approved a township of 1.4 square miles which was later increased to 4.2 miles in 1930 under Act 133(1930). In 1.1.1977 through the power of Act 171(1976) the Township of Malacca was merged with the City Council of Malacca with an administrative power over an area of 114.7 square miles (303 square kilometers).